Suzuki–Miyaura Cross-Coupling Reactions for Increasing the Efficiency of Tris-Heteroleptic Iridium(III) Emitters - Boudreault, Pierre-Luc T; Esteruelas, Miguel A; Mora, Erik; Oñate, Enrique; Tsai, Jui-Yi (Organometallics, 2019)
The complex Ir(acac){κ2-C,N-[C6BrH3-py]}{κ2-C,N-[C6H4-py]} (2) is a green emitter, which displays short lifetimes (0.9–4.9 μs) and quantum yields of 0.32 in poly(methyl methacrylate) films at 5 wt % and 0.41 in 2-methyltetrahydrofuran at room temperature. Its Pd(OAc)2/4 PPh3-catalyzed cross-coupling reactions with RB(OH)2 afford Ir(acac){κ2-C,N-[C6RH3-py]}{κ2-C,N-[C6H4-py]} (R = Me (3), Ph (4)), which show almost identical emissions with quantum yields in the range 0.98–0.82.